(untitled) (Journal of Face Aesthetics, 2021)
This paper presents the possibilities of instrumental diagnosis for assessing the condition of various facial skin areas. Studies were carried out to determine the elasticity of the facial skin and its ability to return to its original shape. Both sides were analyzed: on the left and right side of the face skin parameters in selected areas in women of two age groups. The Cutometer Dual MPA 580 probe was used in the study, with which the parameters R0, R8, and R8 / R0 were determined for a group of 37 younger women (25–40 years old) and a group of 38 older women (40–55 years old). The results obtained for both groups are in the ranges R0 (0.20–0.33) mm, R8 (0.10–0.27) mm, R8 / R0 (66–82)%. It was found that within each age group there are no statistically significant differences between the left and right sides of the face in the parameters studied. For the R8 / R0 ratio, a weak negative correlation with age was found for all measuring points except the points above the top of the mouth, and the highest correlation was found for measuring points located near the eyes.